THE TRANSLATION SHIFTS OF IDIOM IN ENGLISH-INDONESIAN NOVEL ALLEGIANT BY VERONICA ROTH - Ni Luh Kasih Maria; Km Tri Sutrisna Agustia (LPPM Universitas Dhyana Pura, 2016)
ABSTRACTThe title of this paper is “The Translation Shifts of Idiom in English-Indonesian Novel Allegiantby Veronica Roth”. In translating idioms, the translator find a lot of problems, it is come due tothe lack of the equivalence in a different level of idiom. In translation, the shift is a part thatcannot be separated because the purpose of the translation is the transfer of the meaning fromsource language into target language. There are two objectives in this paper; (1) to describe thetypes of idiom (Hocket 1958), (2) to describe the kind of translation shift in idiom (Catford1965). The data of this study are idiomatic expressions occurring in English-Indonesian novelAllegiant by Veronica Roth. The data collecting of this study was done by using library researchand documentation method. Qualitative method was used in the analysis and it was descriptivelypresented. This study found there were 3 types of idiom; they are English Phrasal Compound,Figure of Speech and Slang. The translation shifts found in this novel only in Category Shift,they are structure shift, unit shift and intra-system shift. This study can also be a reference toother researchers to conduct the same topic with different points of view according to theirpurposes, object and usages.Keywords: idiom, translation, translation shift,ABSTRAKSkripsi ini berjudul “The Translation Shifts of Idiom in English-Indonesian Novel Allegiant byVeronica Roth”. Dalam menerjemahkan idiom, banyak permasalahan yang ditemukan olehpenerjemah, hal tersebut karena adanya kekurangan dalam kesetaraan tingkat yang berbedadari suatu idiom. Dalam translation, pergeseran tidak dapat dipisahkan karena tujuannyaadalah untuk mentransfer makna dari bahasa sumber ke dalam bahasa target.ada dua hal yangditeliti, (1) menjelaskan tentang jenis-jenis idiom (Hocket 1958), (2) menjelaskan jenis-jenispergeseran translation di idiom (Catford 1965). Data diambil dari idiom di Novel Allegiant dariVeronica Roth. Pengumpulan data yang digunakan adalah daftar pustaka dan dokumentasi.Metode kualitatif digunakan dalam menganalisa data. didalam skripsi ini ditemukan tiga jenisgaya bahasa, diantaranya English Phrasal Compound, Figure of Speech dan Slang. Pergeserandalam penerjemahan hanya Category Shift diantaranya structure shift, unit shift dan intrasystemshift. Penelitian ini bisa menjadi referensi bagi peneliti lainnya yang berminat dalamdunia penerjemahan.Kata kunci: idiom, penerjemahan, pergerseran penerjemahan